REKRUTMEN KARANG ALAMI SCLERACTINIA DI SEKITAR CORAL GARDEN NUSA DUA REEF FOUNDATION, NUSA DUA, BALI - Sitompul, Kezia Ruth Marganti; Yuni, Luh Putu Eswaryanti Kusuma; Subagio, Job Nico (SIMBIOSIS; Vol 11 No 2 (2023)DO - 10.24843/JSIMBIOSIS.2023.v11.i02.p04, 2023)
Coral reefs are one of the ecosystems that have an important role for humans. Indonesia is a country that has the largest coral reef ecosystem in the world, however, the condition of coral reef cover that is declared to be poor is relatively not small. Nusa Dua is one of Indonesia’s coast chosen for coral rehabilitation. Coral transplantation and its maintenance have been carried out for seven years by the Nusa Dua Reef Foundation (NDRF) at the coral garden , that located in Nusa Dua. This study was conducted to determine the effect of coral garden on recruitment in the surrounding waters by observing the coral recruitment in the area around the NDRF’s coral garden . Coral recruitment was determined by observing the species of recruit and its density. Recruit colony were determined by using the Underwater photo transect Method (UPT). The study resulted that the overall recruit coral density was 0.65 colonies/m2 which was classified as low. The study found 25 colonies of natural coral recruits from seven genus and six families. The recruit species found were Goniastrea sp., Pocillopora damicornis , Porites sp., Stylophora sp.1, Stylophora sp.2, Galaxea fascicularis , Montipora digitate , Psammocora sp. The species most commonly found was Pocillopora damicornis .